The Effect of Village Officials’ Competence and Educational Level on Accountability in the Management of Village Funds - Sri Pebriani Mopatu; Sahmin Noholo; Nilawaty Yusuf (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the effects of village officials’ competence and formal educational level on the accountability of village fund management in Tibawa Subdistrict, Gorontalo Regency. Research Method: This study employed a quantitative approach with a causal design. Data were collected through questionnaires distributed to 96 village officials directly involved in village fund management across 16 villages in Tibawa Subdistrict. Respondents were selected using purposive sampling based on their roles in planning, implementation, administration, reporting, and supervision of village funds. Data were analyzed using SPSS through validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination analysis. Results and Discussion: The findings reveal that village officials’ competence and formal educational level each have a positive and significant effect on the accountability of village fund management. Simultaneously, both variables significantly influence accountability, with the model explaining 72.9% of the variation in accountability. Implications: Strengthening technical competence and improving educational capacity are essential to enhance accountable village financial governance. Originality: This study extends Agency Theory by empirically demonstrating the simultaneous role of competence and formal educational level in reducing agency problems and strengthening accountability in village fund management.